Implementasi Pendidikan Karakter Islami pada Kegiatan Ektrakurikuler "Hizbul Wathan" (Studi Empirik di SMA Muhammadiyah 3 Surakarta Tahun Pelajaran 2016/2017 - Zaenal Arifin, Zayn, Drs. Bambang Raharjo, M.Ag (2017)
In facing the era of the development of science and technology, education is not enough to just put forward the intellectual intelligence, but on the other hand it is necessary to strengthen ethical values, moral and character of learners. The cultivation of the values of the character can be done through extracurricular activities, Hizbul Wathan as extracurricular scouting activities based on Islam, seeks to prepare children, teenagers and youth to have Islamic faith, good mentality, strong physical, have a lot of knowledge and technology, and have good personalities, it's existance in Muhammadiyah schools certainly will further facilitate the inculcation of the values of Islam to the students. Then in this study the authors take a focus on implementation of Islamic character education on Hizbul Wathan activities in Muhammadiyah High School 3 of Surakarta. This study aims to describe the implementation of Islamic character education on Hizbul Wathan extracurricular in Muhammadiyah High School 3 of Surakarta in the academy year 2016/2017. The research is the field research, using interviews, observation and documentation in collecting data, and using interactive method in the process of analyzing data. The results of this research can be summed up as follows: basically the curriculum and activities of HW have loaded the Islamic character values. The Islamic characters developed in the HW Extracurricular in Muhammadiyah High School 3 of Surakarta are all the contents that contained in the character education designed by the Ministry of Education and Culture, such as : a) religious, b) honest, c) responsible d) an avid reader, e) discipline, f) hard work, g) creative, h) curious, i) independent, j) tolerant, k) social care, l) appreciating the work and achievements, m) communicative, n) loving peace, o) democratic, p) the spirit of nationality, and q) loving the country. Each value of Islamic character education implemented through customization of Hizbul Wathan curriculum content which includes some lessons such as Al-Islam and Kemuhammadiyahan, General lesson, the Lesson of Hizbul Wathan, and Lesson of Scouting. Developing the values of Islamic character education in each Hizbul Wathan activity implemented by regular activity, spontaneous activity, example, and conditioning, with approaches that are in accordance with the mandate of the national character education. Recommendation for the next researcher is to conduct advanced research because of the importance of the discussion of Islamic character education on Hizbul Wathan extracurricular still requires further study in order to formulate a new theory regarding the construction of the character values in the Hizbul Wathan extracurricular. Keywords: Islamic Character Education and Hizbul Wathan Extracurricular